Survival 1.0: A Novel Autonomous Industrial Mobile Warehouse (AIMW) for Industrial Environments - Eduardo Garcia; Miguel Montaña; Nicolás Montés (Applied Sciences)
This article presents the design, implementation and start-up of the first AIMW (Autonomous Industrial Mobile Warehouse) in the industry, in particular, in the factory located at Ford España S.L. in Almussafes (Valencia). This first version has been given the name of “Survival”, due to its ability to survive the industrial environment commonly known as “the jungle”. The motivation for the design of the first AIMW was due to the management of spare warehouses for maintenance tasks. In all factories there is a central warehouse where replacement materials with a higher probability of use are placed near the warehouse exit, thus reducing the time to obtain the replacement. However, in large factories, such as automobile manufacturing, the distance between the central warehouse and the place where the breakdown occurs may cause very long delays. For this reason, there are smaller warehouses distributed throughout the plant that replicate the part of the central warehouse where the most used materials are kept. The objective of our research is to make that part of the central warehouse mobile with the AIMW design, thus eliminating the fixed warehouses. In the factory at Ford España S.L. in Almussafes there are 170 of these warehouses distributed in a homogeneous way. In this first proposal of an AIMW, and with the primary objective of reducing costs, Survival 1.0 has been designed based on a commercial AMR. For its choice, commercial AMRs were tested in real situations within the Ford factory (Almussafes). As a result, none of them were able to pass all the tests. In addition, the current regulations for AMRs, the ANSI/ITSDF B56.5:2019 and the EN 1525:1997 standard, only define minimum test standards to describe how manufacturers and users must carry out the safety measurements of AGVs and AMRs. However, from an industry point of view, these regulations are not adequate. Therefore, there are extensions of these regulations generated by the companies themselves that imply additional developments of commercial AMRs. This paper shows the developments made to be able to integrate the first AIMW into the production line, but it also shows the gap between research and standardization of AMRs with respect to the demands and needs of the industry. There are currently three Survival 1.0 AIMWs in operation in the factory at Ford España S.L. in Almussafes.